2019
DOI: 10.3390/plants8110453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Solar Protection Factor (SPF), Antioxidant Activity, and Cell Viability of Mixed Vegetable Extracts from Dirmophandra mollis Benth, Ginkgo biloba L., Ruta graveolens L., and Vitis vinífera L.

Abstract: The aim of this study was to validate a HPLC method for the assay of flavonoids in extracts obtained from natural sources, i.e., from Dirmophandra mollis Benth, Ginkgo biloba L., Ruta graveolens L., and Vitis vinífera L. The potential sun protecting effect, antioxidant activity, and cell viability of the extracts were also determined. Individual extracts (obtained from each individual species) and a mixed extract (containing the four extracts) were analyzed by the validated HPLC method for the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Previous data regarding the antioxidant capacities of sage, rosemary, rue, olive leaf, peppermint, parsley, and pomegranate leaf have been reported by several authors 12 , 14 , 18 , 22 , 26 , 31 , 36 . The IC 50 values of ABTS and DPPH radical scavenging activity, as well as the EC 50 values of reducing powder regarding olive leaves ranged from 20.13 to 190.95 µg mL −1 , from 17.97 to 41.64 µg mL −1 , and from 90 to 216 µg mL −1 , arising from diverse extraction solvents 12 .…”
Section: Resultsmentioning
confidence: 92%
“…Previous data regarding the antioxidant capacities of sage, rosemary, rue, olive leaf, peppermint, parsley, and pomegranate leaf have been reported by several authors 12 , 14 , 18 , 22 , 26 , 31 , 36 . The IC 50 values of ABTS and DPPH radical scavenging activity, as well as the EC 50 values of reducing powder regarding olive leaves ranged from 20.13 to 190.95 µg mL −1 , from 17.97 to 41.64 µg mL −1 , and from 90 to 216 µg mL −1 , arising from diverse extraction solvents 12 .…”
Section: Resultsmentioning
confidence: 92%
“…The interest in natural products as sources of new drugs and therapeutic strategies for chronic diseases is increasingly growing. Among those sources, natural antioxidants from different plants (e.g., Dirmophandra mollis Benth, Ruta graveolens L., Ginkgo biloba L., Vitis vinifera L, Thymus zygis , Croton argyrophyllus Kunth, Hordeum vulgare, Dalbergia ecastophyllum, Origanum vulgare L.) are receiving particular attention [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A red variety of Brazilian propolis has been described in the last years, with the ethanolic extracts being enriched in isoflavones, mainly formononetin, daidzein, and biochanin A [7]. Studies have demonstrated that such hydroalcoholic and ethanolic extracts have potential antitumoral activity both in vitro [8,9] and in vivo [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%